Dr John Thomas: The First Baptist Missionary to Bengal - Whitfield, Michael (Baptist quarterly, 2015)
The short life of Dr John Thomas has been almost forgotten. Possible reasons for this have been stories about his difficult personality that nowadays would perhaps be medically evaluated in a different way. In spite of this, Thomas achieved much by his contribution to the spread of Christianity in Bengal, especially in starting a translation of the Bible and in his medical work. His relationship with William Carey, which many commentators view as negative, can be seen as far from that, and was key to Carey's success in India.